ZAKAT AND ECONOMIC DEVELOPMENT: A PATHWAY TO PROSPERITY AND SOCIAL JUSTICE - Irshad Ahmad Reshi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Zakat, one of the five pillars of Islam, plays a pivotal role in promoting economic development and social justice. This article explores how Zakat functions as a tool for wealth redistribution, poverty alleviation, and economic empowerment, particularly in developing countries. By channeling funds to the poor, small businesses, and infrastructure development, Zakat stimulates economic activity, reduces inequality, and fosters sustainable growth. The article also highlights how modern Islamic economies are institutionalizing Zakat to maximize its impact, creating a system where economic progress and social responsibility are deeply intertwined.